"My Silk Road to You": Re-imagining routes, roads, and geography in contemporary art of "Central Asia". Issue 1 (January 2017) - Kudaibergenova, Diana T.
Abstract: This paper re-focuses the Silk Road discussions from the position of contemporary art in Central Asian region. Since the late 1980s contemporary art in Central Asia boomed and it eventually became an alternative public space for the discussion of cultural transformations, social and global processes and problems that local societies faced. Initially the questions raised by many artists concerned issues of lost identity and lost heritage during the period of Soviet domination in the region. Different artists started re-imagining the concept of the Self in their works and criticising the old rigid approaches to geography, history and mobility. Nomadic heritage became one of the central themes in contemporary art of Central Asia in the 1990s. Artists started experimenting with symbols of mobility, fluid borders and imagined geography of the "magic steppe" (see Kudaibergenova 2017, "Punk Shamanism"). Contemporary art in Central Asia continues to serve as a space for social critique and a space for search and re-conceptualisation of new fluid identities, geographies and region's place on the world map. In this paper I critically evaluate three themes connected to the symbolism of Silk Road heritage that many artists engage with – imagined geography, routes, roads and mobility. All three themes are present in the selected case studies of Gulnara Kasmalieva's and Muratbek Djumaliev's TransSiberian Amazons (2005) and A New Silk Road: Algorithm of Survival and Hope (2007) multi-channel video art, Victor and Elena Vorobievs' (Non)Silk Road (2006) performance and photography, Almagul Menlibayeva's My Silk Road to You video-art and photography (2010–2011), Yerbossyn Meldibekov's series on imagining Central Asia and the Mountains of Revolution (2012–2015), and Syrlybek Bekbotaev's Kyrgyz Pass installation (2014–2015) as well as Defenders of Issyk Kul (2014). I trace how artists modernise, mutate and criticise main discourses about Silk Road and what impact this has on the re-imagination processes.